2015
DOI: 10.3109/09638288.2015.1076529
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of “acceptance” for patients with long-term pain when starting rehabilitation

Abstract: Healthcare professionals should be aware that individuals with long-term pain conceptualize and hold different meanings of acceptance when starting rehabilitation; this should be considered and addressed in rehabilitation programmes. The meaning given to acceptance is related to the experience of the lived body and the sense of self, as well as to getting legitimization/acceptance by others; therefore these aspects need to be considered during rehabilitation. The process of achieving acceptance seems to embrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 105 publications
1
19
0
Order By: Relevance
“…This is a concern because acceptance may imply resignation or giving up to some respondents. For example, a qualitative study in chronic pain patients found that acceptance was perceived by some participants as an empowerment process, while others thought of acceptance as a personal failure [74].…”
Section: Methodological Limitations Of the Included Studiesmentioning
confidence: 99%
“…This is a concern because acceptance may imply resignation or giving up to some respondents. For example, a qualitative study in chronic pain patients found that acceptance was perceived by some participants as an empowerment process, while others thought of acceptance as a personal failure [74].…”
Section: Methodological Limitations Of the Included Studiesmentioning
confidence: 99%
“…They were also invited to dance their 'yes' and 'no' during this rhythm which gave insights in how to find decisiveness in the dance as well as in life. Biguet et al [43] states that the aspects of acceptance need to be considered during physiotherapy rehabilitation as the meaning given to acceptance is related to the experience of the lived body and the sense of self, as well as getting legitimacy/acceptance by others. The informants expressed appreciation that their physiotherapist could listen to the needs of the group and guide them in accordance with this intuitive listening in the subtheme.…”
Section: Discussionmentioning
confidence: 99%
“…Prioritizing personal strength and focusing on what is pleasurable in life, instead of situations where the pain dominates, can thus be of importance here. This can be referred to as empowerment, which has been highlighted as a coping mechanism for chronic pain in other studies [30,31].…”
Section: Personal Attributesmentioning
confidence: 98%